Design of a Fast Location-Based Handoff Scheme for Vehicular Networks - Wang, Yikun (Université d'Ottawa / University of Ottawa, 2013)
IEEE 802.11 is an economical and efficient standard that has been applied to vehicular networks. However, the long handoff latency of the standard handoff scheme for IEEE 802.11 has become an important issue for seamless roaming in vehicular environments, as more handoffs may be triggered due to the higher mobility of vehicles. This thesis presents a new and fast location-based handoff scheme particularly designed for vehicular environments. With the position and movement direction of a vehicle and the locations of the surrounding APs, our protocol is able to accurately predict several possible APs that the vehicle may visit in the future and to assign these APs different priority levels. APs on higher priority levels will be first scanned. Once a response to scanning from an AP is received, the scanning process ends immediately. A blacklist scheme is also used to exclude those APs that showed no response to the scanning during previous handoffs. Thus, time spent on scanning APs is supposed to be significantly reduced. The simulation results show that the proposed scheme attains not only a lower prediction error rate, but also a lower MAC layer handoff latency, and that it has a smaller influence on jitter and throughput; moreover, these results show that the proposed scheme has a smaller total number of handoffs than other handoff schemes.
Keywords: handoff; vehicular networks; IEEE 802.11